Optimizing sweet potato production: insights into the interplay of plant sanitation, virus influence, and cooking techniques for enhanced crop quality and food security - Villalba, Anna; Martínez-Ispizua, Eva; Morard, Miguel; Crespo-Sempere, Ana; Albiach-Marti, María R.; Calatayud, Angeles; Penella, Consuelo (Frontiers in Plant Science, 2024)
This study investigates the impact of sweet potato plant sanitation on the yield and external and internal quality root storage exploring the nutritional content affected by various cooking methods (raw, boiled, and oven-cooked). The presence of viruses, and concretely of the Sweet Potato Leaf Curl Virus (SPLCV), in sweet potato propagation material is shown to significantly reduce yield and modify storage root quality. Notably, the research reveals a substantial improvement in crop yield and external quality, reinforcing the efficacy of plant sanitation methods, specifically apical meristem culture, in preserving the overall productivity of sweet potato crops. Furthermore, the investigation identifies a noteworthy decrease in starch content, suggesting a dynamic interaction between plant sanitation and starch metabolism in response to viral diseases. The study also delves into the alteration of mineral absorption patterns, shedding light on how plant sanitation influences the uptake of essential minerals in sweet potato storage roots. While the health status of the plants only slightly affected magnesium (Mg) and manganese (Mn) accumulation, indicating a potential resilience of mineral balance under virus-infected conditions. Moreover, the research identifies significant modifications in antioxidant levels, emphasizing the role of plant sanitation in enhancing the nutritional quality of sweet potatoes. Heat-treated storage roots, subjected to various cooking methods such as boiling and oven-cooking, exhibit notable differences in internal quality parameters. These differences include increased concentrations of total soluble solids (SS) and heightened levels of antioxidant compounds, particularly phenolic and flavonoid compounds. The observed increase in antioxidant capacity underscores the potential health-promoting benefits associated with plant sanitation practices. Overall, the study underscores the critical importance of plant sanitation in enhancing sweet potato production sustainability, contributing to food security, and supporting local agricultural economies. The results emphasize the need for further research to optimize plant sanitation methods and promote their widespread adoption globally, providing valuable insights into the complex relationships in food quality..